Is deregulation necessary? The effects of employment protection on unemployment - Avdagic, Sabina (Bratislava, 2010)
"Using new data, the paper examines the effect of employment protection legislation (EPL) on aggregate and youth unemployment in advanced OECD economies and in Central and Eastern Europe during 1980-2009. The analysis assesses both the direct and indirect effects of EPL on levels of unemployment, as well as the short-term and long-term effects of changes in EPL on changes in unemployment. The results offer no clear support for the argument that EPL is a cause of either aggregate or youth unemployment. While EPL reaches statistical significance at conventional levels in some models, the results are sensitive to small changes in the sample or the use of alternative estimators. The only finding that appears robust concerns the interaction between EPL and the tax wedge, which suggests some scope for reform complementarity in tackling youth labour market problems. On the whole, the analysis suggests that government efforts to tackle unemployment by deregulating EPL alone may well be unwarranted."